A different gut microbial community between larvae and adults of a wild bumblebee nest (Bombus pascuorum). (7th November 2016) - Parmentier, Anneleen; Meeus, Ivan; Van Nieuwerburgh, Filip; Deforce, Dieter; Vandamme, Peter; Smagghe, Guy
Abstract: Although the gut microbial communities in adult bumblebees and their associated functionalities are widely studied, descriptive data on the larval gut microbiota are still limited. The gut microbiota of a fully sampled wild Bombus pascuorum nest has been characterized, using the multiplexed Illumina MiSeq 16S ribosomal RNA amplicon sequencing technique. The nesters and foragers inhabiting the same nest showed the typical core bacterial sequences and only marginal differences in their characterized gut microbiota. The gut microbial communities within the adult and larval specimens differed strongly, as the typical core gut bacteria in the adult bumblebees are absent in the larval bumblebees. The bacterial communities within the larval gut are dominated by bacterial phylotypes of Enterobacteriaceae and Lactobacillaceae, supplemented with genera belonging to Corynebacteriales and Bacillales . The function of this larval gut microbiota, being different from the adult, remains to be determined.